2015
DOI: 10.1177/0363546515608477
|View full text |Cite
|
Sign up to set email alerts
|

Micheli Anterior Cruciate Ligament Reconstruction in Skeletally Immature Youths

Abstract: At a mean 3-year follow-up, the study findings confirmed excellent functional outcomes, a low ACL revision rate, and no growth disturbances. Patients returned to their preoperative activity level after reconstruction. This procedure offers a safe and effective ACL reconstruction option in children with several years of growth remaining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…A pediatric-specific PROM, the Pediatric International Knee Documentation Committee (Pedi-IKDC) subjective knee form, 26 was reported in 1 of the 17 studies. 48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pediatric-specific PROM, the Pediatric International Knee Documentation Committee (Pedi-IKDC) subjective knee form, 26 was reported in 1 of the 17 studies. 48 …”
Section: Resultsmentioning
confidence: 99%
“… 39 That said, only 1 study from our sample incorporated a pediatric-specific, validated instrument. 48 Recently developed pediatric-focused knee and activity PROMs may have a widespread impact if appropriately used for future clinical outcomes assessments in this demographic. 16 , 17 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Pedi-IKDC (Pediatric IKDC) and Lysholm scores averaged 93 points each. Clinical success has been replicated in other series as well 104,105 . Twenty-two knees at a mean follow-up of 3.0 years had mean Pedi-IKDC and Lysholm scores of 96.5 and 95 points, respectively, with high patient satisfaction, no limb-length or angular deformities, and 3 knees (14%) that required revision ACL surgery 105 .…”
Section: Physeal Sparing: Extraphyseal Iliotibial Band Autograft Recomentioning
confidence: 80%
“…The rate of ACL graft failure was 4.5%, and no growth disturbances were reported 51,52. Willimon et al57 described similar low graft failure rates with no growth disturbances, adding that patients were successful at return to sports after iliotibial band ACL reconstruction. Despite being a nonanatomic reconstruction, biomechanical studies have shown that it best replicates the intact ACL 58,59.…”
Section: Treatmentmentioning
confidence: 89%